(untitled) (Tempo e Argumento, 2023)
The Sala das Promessas in the Shrine of Aparecida features a huge and heterogeneous selection of ex-votos (offers given by believers as thanks for alleged graces granted by the Virgin) whose exhibition is organized by sectors and themes. The compilation, in general, is temporary: the reception of ex-votos (promessas) takes place in a ‘desk’ where the offering people (believers who visit the basilica) deliver them, in supports as varied as their themes. We recognize certain categories or types of objects (some of serial and industrial production that are sold in the surroundings, others are handmade or very personal). The proposal is to think through the Sala das Promessas as a museum and, consequently, as a cultural device that refers to a network of heterogeneous elements (with a certain unity or axis in the religious theme and, within it, in an imaginary ‘pact’ between the offering people and the Virgin, mediated by the Church) in which individuals, devices, and subjectivation processes make religious discourses and practices intertwine in the building of meanings, knowledge, and legitimacy. The existence of this network in the museological space allows us to think about the relations of representation in Brazilian Catholicism and the practices that produce and reproduce beliefs in relation to the Virgin’s image and power. In the practice of leaving ex-votos and in the exhibition mode, power and legitimacy are constituted: subjectivation of a religious nature is produced for various players linked to each other, in an actual scenario.